Emotions in Plato - Candiotto, Laura,; Renaut, Olivier, (Brill's Plato Studies Series ;, 2020)
Emotions ( pathè ) such as anger, fear, shame, and envy, but also pity, wonder, love and friendship have long been underestimated in Plato's philosophy. The aim of Emotions in Plato is to provide a consistent account of the role of emotions in Plato's psychology, epistemology, ethics and political theory. The volume focuses on three main issues: taxonomy of emotions, their epistemic status, and their relevance for the ethical and political theory and practice. This volume, which is the first edited volume entirely dedicated to emotions in Plato's philosophy, shows how Plato, in many aspects, was positively interested in these affective states in order to support the rule of reason.